(untitled) (Jurnal Bahasa, 2009)
This article discusses the transformation of biological terminologies in three different decades (1960’s, 1980’s and 1990’s). The study focuses an translated and borrowed terms in view of the/act that biology is an imported field, hence the requirement of a borrowed concept. This study aims to examine the existence of particular patterns in establishing the terminology of three different decades. It also attempts to look at the language attitude of society towards the terms in Malay language. The methodology in this research includes the usage of textbooks on terminology and DBP Corpus Database. Istilah Kajihayat, Perhutanan dan Pertanian (1968), Istilah Biologi (1988) and DBP Corpus Database were used as data source. The finding shows that between the 1969-1988 period, more than 80 percent of the studied terms faced a transformation that could be characterised in five categories. Subsequently, this research shows that only five percent of these terms have evolved in 1990’s. The factors that cause the transformation have been identified. The acceptance and utilization through books and newspapers indicate the positive attitudes of society towards the terms used. In addition, the different patterns of terminology usage in the period under review have been successfully identified.